Propriedades antioxidantes do feno de Moringa Oleifera LAM. e seu efeito sobre a capacidade reprodutiva de carneiros - Silva, Michele Pereira da (2024)
Moringa oleifera hay (MO-H) may represent an important source of compounds with antioxidant action for the diets of breeding rams, helping to prevent damage from reactive oxygen species on spermatozoa. This study aimed to evaluate the antioxidant properties of diets with MO-H and their effect on the reproductive potential of rams. There were used 28 rams, divided in four groups (G) submitted to experimental isonitrogeneus diets composed of 30% concentrate (CC) (corn, soybean meal and urea); plus a different proportions of sorghum silage (SS) and MO-H, where: G0 (control: 0% MO-H, 70% SS); G10 (10% MO-H, 60% SS); G20 (20% MO-H, 50% SS); G30 (30% MO-H, 40% SS). Water and mineral salt for sheep were offered ad libitum. Chemical-bromatological analyzes of the components of the diets and leftovers were carried out. Analysis of bioactive, phenolics and flavonoids compounds, antioxidant capacity by DPPH radical scavenging, ABTS radical uptake and iron reduction by the FRAP method were carried out on fresh Moringa (MO) and MO-H samples. FRAP analyzes were also carried out in seminal plasma to evaluate its total antioxidant capacity. Every 15 days, for 60 days, the rams were weighed to control weight development and semen was collected for seminal (volume, sperm concentration and total number of sperm) and semen analyzes (motility, vigor, morphology, integrity, plasma membrane functionality and acrosome integrity). MO-H did not differ from MO regarding total phenolics. The flavonoid content was higher in MO-H than in MO (4.75 vs. 3.88 mg Eq CAT/g). DPPH, ABTS and FRAP analyzes revealed high antioxidant capacity and high reducing power of MO-H. The total antioxidant capacity of seminal plasma did not differ among the experimental groups. From the semen analyses, differences were observed among the groups only in terms of sperm integrity: groups of rams having F-MO in the diet regardless of concentration (G10, G20 and G30) showed a higher percentage compared to G0. It is concluded that haying enhances the antioxidant capacity of Moringa oleifera and that its presence in the composition of diets increases the reproductive potential of rams.